Hubungan Self-Awareness Perawat Dengan Pemilahan Sampah Medis Di Ruang Rawat Inap Rumah Sakit Jiwa Provinsi Bali - Lesminiantini, Ni Wayan; Aryana, I Ketut; Rusminingsih, Ni Ketut; Sujaya, I Nyoman; Sali, I Wayan (Jurnal Kesehatan Lingkungan (JKL), 2025)
. Hospitals generate waste, both medical and non-medical waste that can cause disease in the surrounding environment pollution, an important role is needed for nurses in the management of infectious waste because they are the producers of medical waste from health service activities. Nurses' self-awareness plays an important role in sorting medical waste. This study aims to determine the relationship between nurses' self-awareness and sorting medical waste at the Bali Provincial Mental Hospital. The type of research was correlation analytic with a cross sectional approach. The research sample was nurses in the Bali Provincial Mental Hospital Inpatient Room, sampling that met the inclusion criteria of 100 people with proportional random sampling technique. The types of data used were primary and secondary data. Data processing with Spearman Rank test. The results showed that nurses' self-awareness was mostly in the good category, as many as 44 people (44%). The sorting of medical waste by nurses is mostly in the good category as many as 46 people (46%). There is a significant relationship between nurses' self-awareness and sorting of medical waste in Bali Province Mental Hospital. The results of the Rank Spearman test also obtained a coefficient corelation value of 0.949 indicating a strong correlation with a positive direction that the better the nurse's self-awareness, the better the sorting of medical waste. It is recommended to nurses to pay attention to behaviour when sorting waste when it will be disposed of in the appropriate waste bin.